2017
DOI: 10.1007/s00038-017-0982-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of poverty and social exclusion with body mass index among Special Olympics athletes in Europe

Abstract: 10Objectives: To examine the association of a risk of poverty and social exclusion (AROPE), age, and 11 gender with the Body Mass Index (BMI) status of European Special Olympics athletes. 12Methods: BMI records were available for 1,905 children and youth and 5,517 adults from the Special 13Olympics International (SOI) Health Promotion database. AROPE was extracted from EU Eurostat 14 statistics. Logistic regression analyses were used to predict BMI status. 15Results: For children/youth and adults respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Increasing age was significantly associated with the presence of high BMI. This relationship has consistently been observed in both international and North American SO athletes (Foley et al, 2013;Foley et al, 2017;Rintala et al, 2017;Temple et al, 2014). Furthermore, 50.3% of the sample in the present study exhibited high BMI, comparable to obesity rates among SO athletes in the U.S. (Foley et al, 2013) and North America (Temple et al, 2014).…”
Section: Body Mass Indexsupporting
confidence: 86%
See 2 more Smart Citations
“…Increasing age was significantly associated with the presence of high BMI. This relationship has consistently been observed in both international and North American SO athletes (Foley et al, 2013;Foley et al, 2017;Rintala et al, 2017;Temple et al, 2014). Furthermore, 50.3% of the sample in the present study exhibited high BMI, comparable to obesity rates among SO athletes in the U.S. (Foley et al, 2013) and North America (Temple et al, 2014).…”
Section: Body Mass Indexsupporting
confidence: 86%
“…Research utilizing this dataset have consistently shown SO athletes to exhibit high rates of obesity (Foley et al, 2013;Foley et al, 2017;Rintala et al, 2017;Temple et al, 2014). Older age and sex (i.e., being female) have consistently been associated with obesity in SO athletes in North America (Foley et al, 2013;Temple et al, 2014) and internationally (Foley et al, 2017;Rintala et al, 2017). Furthermore, both male and female athletes exhibit higher rates of obesity than adults in the general population in the U.S. (Foley et al, 2013).…”
Section: Special Olympicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The health information gathered on individual athletes has been aggregated into the world's largest dataset focused on the health of people with intellectual disabilities (Lloyd, Foley, & Temple, ). Preliminary analyses by Rintala, Temple, Lloyd, Faro, and Foley () have demonstrated the feasibility of using this data to address issues of obesity in a European context.…”
Section: Introductionmentioning
confidence: 99%
“…SOI has been hosting free Healthy Athlete screenings at local, national and international competitions (Lloyd, Temple, & Foley, 2012;. Gathering of such data has been integral in the investigation of the health status of participating athletes and has allowed researchers to analyze this population in hopes of initiating interventions to increase healthy behaviors (Rintala, Temple, Lloyd, Faro, & Foley, 2017). The purpose of this study was to examine the physical activity frequency of children and youth with ID who participate in Special Olympics across economic status.…”
Section: Introductionmentioning
confidence: 99%